Lack of Visual Field Improvement After Initiation of Intraocular Pressure Reducing Treatment in the Early Manifest Glaucoma Trial - Bengtsson, Boel (Invest Ophthalmol Vis Sci, 2016)
PURPOSE: We evaluate how visual fields are affected by the initiation of IOP-reducing therapy in previously untreated glaucoma individuals. METHODS: Qualifying individuals with newly diagnosed glaucoma having normal to moderately elevated IOP were prospectively randomized either to IOP-reducing therapy or to no treatment. Before randomization, individuals underwent repeatedly Standard Automated Perimetry (SAP) testing and Goldmann tonometry. Three months after randomization, patients again underwent SAP and tonometry. Changes between baseline and the 3-month follow-up visit in the perimetric summary index, mean deviation (MD), and total deviation values at significantly depressed test points were compared between the treated and untreated groups. RESULTS: Of 255 individuals studied, 129 were randomized to treatment and 126 to no treatment. Intraocular pressure decreased by an average of 24% among treated and by 0.6% in the untreated patients. Mean deviation deteriorated slightly in both groups; mean change was −0.15 and −0.44 dB in the treated and untreated groups, respectively; the difference was not statistically significant, (P = 0.16). No association was seen between IOP reduction and change in MD. Sensitivities decreased slightly in significantly depressed test points, mean change was −0.45 dB in the untreated and −0.38 dB in the treated groups (P = 0.88). CONCLUSIONS: Observed visual field changes among glaucoma patients receiving initial IOP-reducing therapy were not significantly different to changes seen in patients who received no treatment. Thus, our results did not support the idea that visual field status improves after initiation of IOP- reducing therapy in glaucoma individuals, at least not in individuals with initially normal to moderately elevated IOPs.